Interests and corruption - Joković, Milica S (Sociološki pregled, 2017)
This paper analyses the connection of interests and corruption, especially corruption and political interests. It first considers the notion of interest, i.e. its meanings and significance, both for an individual and for a society. It presents the classification if interests by Albion Woodbury Small. A special emphasis is given to the encounter of different interests as the beginning of clash between humans. The paper analyses individual, special and general interests, as well as their relations. The paper also analyses two levels of conflict of interest: the conflict between public and private interest and the conflict between interests within the public offices. The relation of interests in society and politics is solved in the best way by adopting laws, i.e. by introducing the rule of law into political order. Without that the interest orientation of politicians can easily end up in abuse and illegality. In turn, abuses and illegalities open the possibilities for various kinds of corruptive acts.